PFAPA syndrome: new clinical aspects disclosed. Issue 12 (4th April 2006) - Tasher, D; Somekh, E; Dalal, I
Abstract : Background: The recently described PFAPA (Periodic Fever, Aphthous stomatitis, Pharyngitis and Adenitis) syndrome is characterised by periodic fever, aphthous stomatitis, pharyngitis and adenitis. However, there are currently relatively few data on the natural history of this syndrome. Objective: To describe the presentation, clinical course, doctors' awareness, therapeutic response and long-term follow-up of children with PFAPA syndrome. Methods: Children with PFAPA syndrome referred over a 5-year period (from January 1999 to January 2004) were enrolled in the study. Data were gathered from medical records, parents' interviews, physical examination and telephone calls. Results: 54 patients with PFAPA syndrome were evaluated. Our patients had a higher rate of abdominal pain (65%) and a lower rate of aphthous stomatitis (39%) than those in previous reports. Four different patterns of disease evolution were identified, including the relatively common (n = 14, 26%) and newly described course of alternating remissions and relapses. The remissions lasted 8.5 months on average (range 4–36 months). Diagnosis was established by primary paediatricians in 30 of 54 (56%) patients. However, a substantial delay in diagnosis was apparent (mean 15 months). Episodes were curtailed by a much lower dose of prednisone or equivalent corticosteroid (mean 0.6 mg/kg/day, range 0.15–1.5 mg/kg/day) than reported previously. Tonsillectomy was successful in the prevention of recurrence of further episodes in all six patients who underwent the procedure. Conclusions: We describe several new characteristics of PFAPA syndrome in children, contributing to our knowledge of this relatively unrecognised but troublesome syndrome. Early diagnosis and appropriate treatment can markedly improve the quality of life of both patients and families.